Analisis Semiotika Roland Bartners Pesan Dakwah Dalam Film Perjalanan Pembuktian Cinta - Ayu Sawitri; Hasan Sazali (Fakultas Agama Islam Universitas Billfath, 2024)
This study seeks to examine and elucidate the da'wah messages present in the film via the lens of Roland Barthes' semiotic theory. The primary emphasis of the research pertains to communications concerning faith, sharia, ethics, and worship. This research employs a descriptive qualitative methodology, utilizing data collection approaches such as examination of textual content, documents, photographs, and literature review. The acquired data was processed utilizing Nvivo 12 Pro software, which facilitates coding and symbolic interpretation of semiotic aspects in the film. The research findings indicate that the film